Prediction of Deep Vein Thrombosis after Elective Hip Replacement Surgery by Preoperative Clinical and Haemostatic Variables: The ECAT DVT Study - Lowe, Gordon D. O.; Haverkate, Frits; Thompson, Simon G.; Turner, Rebecca M.; Bertina, Rogier M.; Turpie, Alexander G. G.; Mannucci, Pier M.; on behalf of the ECAT DVT Study Group (Thrombosis and Haemostasis, 1999)
The European Concerted Action on Thrombosis (ECAT) DVT Study was a collaborative study of preoperative haemostatic tests in prediction of DVT (diagnosed by routine bilateral venography) after elective hip replacement. 480 patients were recruited in 11 centres across Europe. Clinical risk factors were assessed, and stored citrated plasma aliquots were centrally assayed for 29 haemostatic factors according to the ECAT methodology. 120 (32%) of 375 evaluable patients had DVT, and 41 (11%) had proximal DVT. Among clinical variables, DVT was significantly associated with increased age, obesity, and possibly non-use of stockings. Of the 29 haemostatic factors, mean preoperative levels were significantly higher in patients with subsequent DVT (on univariate analyses) for factor VIII activity, prothrombin fragment F1+2, thrombin-antithrombin complexes, and fibrin D-dimer; and significantly lower for APTT and APC sensitivity ratio. Factor V Leiden was also associated with DVT. Most of these variables were also associated with age, while D-dimer was higher in patients with varicose veins. On multivariate analyses including clinical variables, only a shorter APTT (locally but not centrally performed) and APC resistance showed a statistically significant association with DVT.We conclude that (a) DVT is common after elective hip replacement despite prophylaxis; (b) the study provides some evidence that DVT is associated with a preoperative hypercoaguable state; and (c) preoperative haemostatic tests do not add significantly to prediction of DVT from clinical variables, with the possible exception of APC resistance.